A polygenic risk score improves risk stratification of coronary artery disease: a large-scale prospective Chinese cohort study. (23rd February 2022) - Lu, Xiangfeng; Liu, Zhongying; Cui, Qingmei; Liu, Fangchao; Li, Jianxin; Niu, Xiaoge; Shen, Chong; Hu, Dongsheng; Huang, Keyong; Chen, Jichun; Xing, Xiaolong; Zhao, Yingxin; et al.
Abstract: Aims: To construct a polygenic risk score (PRS) for coronary artery disease (CAD) and comprehensively evaluate its potential in clinical utility for primary prevention in Chinese populations. Methods and results: Using meta-analytic approach and large genome-wide association results for CAD and CAD-related traits in East Asians, a PRS comprising 540 genetic variants was developed in a training set of 2800 patients with CAD and 2055 controls, and was further assessed for risk stratification for CAD integrating with the guideline-recommended clinical risk score in large prospective cohorts comprising 41 271 individuals. During a mean follow-up of 13.0 years, 1303 incident CAD cases were identified. Individuals with high PRS (the highest 20%) had about three-fold higher risk of CAD than the lowest 20% (hazard ratio 2.91, 95% confidence interval 2.43–3.49), with the lifetime risk of 15.9 and 5.8%, respectively. The addition of PRS to the clinical risk score yielded a modest yet significant improvement in C-statistic (1%) and net reclassification improvement (3.5%). We observed significant gradients in both 10-year and lifetime risk of CAD according to the PRS within each clinical risk strata. Particularly, when integrating high PRS, intermediate clinical risk individuals with uncertain clinical decision for intervention would reach the risk levels (10-year of 4.6 vs. 4.8%, lifetime of 17.9 vs. 16.6%) of high clinical risk individuals with intermediate (20–80%) PRS. Conclusion: The PRS could stratify individuals into different trajectories of CAD risk, and further refine risk stratification for CAD within each clinical risk strata, demonstrating a great potential to identify high-risk individuals for targeted intervention in clinical utility. Structured Graphical Abstract: Structured Graphical Abstract The polygenic risk has a great potential to refine CAD risk stratification within each guideline-recommended clinical risk category and inform clinical decision making for primary prevention. Among individuals at intermediate clinical risk whose guideline-based recommendations are unclear, those with high polygenic risk should be recommended to initiate lifestyle and pharmacological intervention. Individuals with both high polygenic risk and high clinical risk urgently need intensive prevention. Combination of polygenic risk and clinical risk could promote precision prevention of CAD and reduce the disease burden, particularly considering inadequate primary prevention or statins and antihypertensive treatment in China.